Vattenkompetensen hos lågstadieelever i årskurserna 4-6 - Lindholm, Matilda (2025)
Water competence is an important skill that involves the ability to manage and move safely in aquatic environments. It also includes knowledge components to better understand how and why to move in a certain way in aquatic environments and to recognize risks and dangers in various situations. The aim of the study was to investigate the level of water competence among fourth, fifth, and sixth graders. The study also examined differences between grades and whether there was gender-based differences in various areas.